Elective re‐intubation to treat complete left lung collapse following Tetralogy of Fallot repair in a very young child - Nirmal Panthee; Battu Kumar Shrestha; Sidhartha Pradhan; Raamesh Koirala; Bishow Pokhrel; Abhishek Chaurasiya; Amita Paudel; Rumi KC (Clinical Case Reports, 2022)
Abstract An 18‐month‐old boy weighing 6 kilograms developed complete collapse of left lung following total correction of Tetralogy of Fallot on the next day of extubation. He received extensive chest physiotherapy, along with lung recruitment maneuver by using bubble CPAP, which failed to show any improvement in lung expansion in 2 days. He was then electively intubated on 3rd postoperative day (POD3) for the purpose of suctioning tracheobronchial secretions and maintaining positive airway pressure to open up the left lung. Good results were obtained immediately after intubation, and he was extubated 9 h later. His lung showed complete aeration afterward. He was transferred out of ICU on POD5 and discharged home on POD10.